Daytime sleepiness, sleep time and social jetlag in undergraduate students - Morales-Sánchez, Ana Karen (2023)
Introduction: Daytime sleepiness has been associated with several factors such as sleep quality, sleep hours and regularity. However, daytime sleepiness studies seldomly consider activity as a relevant variable (comparing working days vs. weekends). Aim: To study the relationship between sleeping hours, social jetlag and daytime sleepiness in undergraduate students. Methods: Participants responded to an online questionnaire, in order to gather sleep hours and daytime sleepiness (using the Epworth Scale). Results: Significant differences were observed in sleep hours during working days and weekends (t(225) = 13.660; p < .001; d = 1.05) as well as negative correlations between daytime sleepiness and sleep hours. Discussion: Further studies are needed with a more thorough variable control, considering study areas as well as chronotypes.